Chemical composition of the essential oil extracted from the leaves and fruits of the plant (smilax aspera L) in Qadmus – Tartous- Syria (Latakia University Journal -Basic Sciences Series, 2021)
the essential oil was extracted by using hydrodistillation (CLEVENGER  APPARATUS)  from leaves and fruits of Smilax aspera, the plant belongs to the Smilacaceae family in temperate and subtropical regions, identifying the chemical composition was done by gas chromatography technique associated with the mass spectrometry GC / MS.The results of the analysis showed that the essential oil of fruits contains 34 compounds, which accounted for 96,8194% of the total aromatic oil. It was found that the compound Octadecene is the main component of aromatic oil by 12.9308%.   As for the aromatic oil extracted from the leaves. 14 compounds was identified, which accounted for about 99,9995% of the total aromatic oil, and was found that the compound 6,9-Pentadecadien-1-ol  is the main component of aromatic oil by 25.9431%.